2006
DOI: 10.1002/art.21800
|View full text |Cite
|
Sign up to set email alerts
|

Lupus‐like disease and high interferon levels corresponding to trisomy of the type I interferon cluster on chromosome 9p

Abstract: Trisomy of the type I IFN cluster of chromosome 9p was associated with lupus-like autoimmunity and increased IFNalpha/beta and IFN receptor signaling. The data support the idea that abnormal regulation of type I IFN production is involved in the pathogenesis of SLE.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
24
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 42 publications
(25 citation statements)
references
References 42 publications
(62 reference statements)
1
24
0
Order By: Relevance
“…As shown by the observation of an IFN signature, it appears that mosaic tetrasomy 9p results in an increased expression of genes induced by IFN, which is in accordance with the findings of Zhuang et al 13 who reported SLE-like disease associated with elevated levels of IFN-a/b in 2 patients with a trisomy of 9p-containing type I IFN cluster. Our report supports the hypothesis that several copies of the type I IFN cluster result in high levels of type I IFN due to a gene-dosage effect, and hence an increased susceptibility to some autoimmune diseases.…”
Section: Figuresupporting
confidence: 90%
“…As shown by the observation of an IFN signature, it appears that mosaic tetrasomy 9p results in an increased expression of genes induced by IFN, which is in accordance with the findings of Zhuang et al 13 who reported SLE-like disease associated with elevated levels of IFN-a/b in 2 patients with a trisomy of 9p-containing type I IFN cluster. Our report supports the hypothesis that several copies of the type I IFN cluster result in high levels of type I IFN due to a gene-dosage effect, and hence an increased susceptibility to some autoimmune diseases.…”
Section: Figuresupporting
confidence: 90%
“…29 Furthermore, 129Sv mice deficient for interferon alpha receptor (IFNAR) are protected from experimental lupus 30 and IFN-a therapy for unrelated disorders is associated with autoimmune manifestations, including lupus-like symptoms. 31 We hypothesized that the SLE-associated increase in CD56 bright NK cell proportion described here could be induced by high IFN-a levels.…”
Section: Discussionmentioning
confidence: 99%
“…Global gene expression studies on blood lymphoid cells and kidneys from SLE patients have shown that IFN-regulated genes (IFN-signature) are selectively upregulated in these patients [158,161]. Some typical lupus symptoms have been described in individuals with trisomy of the type I IFN gene cluster [162] and with single nucleotide polymorphisms in the IRF5 and tyrosine kinase 2 (TYK2) genes, the products of which are involved in regulating type I IFN production [163, Cell. Mol.…”
Section: Dcs and Autoimmunitymentioning
confidence: 99%